Pengaruh Perubahan Kebijakan Tarif PPh Pasal 21 Dan Kepatuhan Wajib Pajak Terhadap Penerimaan Pajak Penghasilan Orang Pribadi Pada KPP Pratama Palembang Ilir Timur - Financy, Adinda Labiba Ufairah; Aziatul Pebriani, Reny; Meiriasari, Vhika (JURNAL ONLINE INSAN AKUNTAN; Vol 9 No 2 (2024): Jurnal Online Insan Akuntan (Desember 2024), 2024)
This research aims to examine the effect of changes in Article 21 Income Tax Tariff Policy and Taxpayer Compliance on Personal Income Tax Receipts at KPP Pratama Palembang Ilir Timur. A total of 36 respondents were collected by distributing questionnaires to tax officers at the East Palembang Ilir Pratama Tax Service Office using a saturated sampling technique. The analysis used in this research is a quantitative method. In this research, 2 independent variables were used, namely changes in tariff policy and taxpayer compliance. There is 1 dependent variable, namely personal income tax receipts. The data used in this research is primary data obtained by distributing questionnaires to respondents. The results of the analysis show that partially the influence of changes in the PPh Article 21 rate policy has an influence on personal income tax revenue at the Palembang Ilir Timur KPP Pratama, while taxpayer compliance has no effect on personal income tax revenue at the Palembang Ilir Timur Pratama KPP. Simultaneously, the Effect of Changes in Article 21 Income Tax Rate Policy and Taxpayer Compliance Affects Personal Income Tax Revenue at KPP Pratama Palembang Ilir Timur.   Keywords: Rate Changes, Compliance Taxpayer, Tax Revenue.